Vulneración de Derechos Constitucionales en la aplicación de sanciones impuestas a servidores de seguridad penitenciaria, en pleno cumplimiento de su deber y los problemas de amotinamiento en las cárceles del Ecuador - Neira Vega, Anthony David (2022)
This degree research work is entitled: "Infringement of Constitutional Rights in the application of sanctions imposed on prison security officers in the full performance of their duty and the problems of riots in Ecuadorian prisons", and its interest to develop is due to the fulfilment of a study in view of the progressive and rational use of force by prison officers to people deprived from freedom because they are within their competence to use it to control and extinguish illegal actions such as riots within the social rehabilitation center. The study shows that the factors that limit the full exercise of duty and endanger the rights of prison security officers in the work context are due to the fact that in their relations and interrelations with the persons deprived of liberty, there are different ways of behaving as a consequence of the conditions in which the prison security officers, not having a legal support, endanger their lives and cannot perform their duties effectively or fulfill their functions and responsibilities to protect, control, reestablish order and provide security inside the social rehabilitation centers. In the present thesis, materials and methods were applied that allowed the development of the investigation, as well as interviews, surveys to legal professionals and surveys to prison security officers, whose results served to demonstrate that there is a violation in those of prison officers who are in full compliance with their duties and to propose the legal reform project to the Organic Integral Penal Code in Art. 293 in relation to accomplish a framework of action for prison security officers, who attached to their area of competence can act more firmly to control cases of riots or other acts or actions of disorder that may affect the members of security as persons deprived of liberty.